Ask Questions, Get Answers


If$ -i+3 $ is a root of $x^{2}-6x+k=0 $ then the value of $k$ is

\[\begin{array}{1 1}(1)5&(2)\sqrt{5}\\(3)\sqrt{10}&(4)10\end{array}\]

1 Answer

The given root is
$\alpha= -i+3$
The other root is
$\beta =i+3$
Sum $ \alpha + \beta =-i +3 +i+3$
$\qquad= 6$
Product $\alpha \beta = (-i +3)(i+3)$
$\qquad= 3^2-i^2$
$\qquad= 9+1=10$
The quadratic equation is
$x^2$ -(sum of the roots)x + product of the roots=0
comparing o the equation
Hence 4 is the correct answer.
answered May 15, 2014 by meena.p

Related questions